2015
DOI: 10.1177/1359105315610812
|View full text |Cite
|
Sign up to set email alerts
|

The process of posttraumatic growth in individuals with traumatic spinal cord injury in Mainland China: An interpretative phenomenological analysis

Abstract: This study aims to explore the process of posttraumatic growth for individuals who have sustained a traumatic spinal cord injury. Semi-structured interviews were conducted with 12 participants with spinal cord injury from the local community. Interviews were recorded on audiotape and transcribed verbatim. Transcripts were analyzed using interpretative phenomenological analysis. Three superordinate themes emerged: struggling in hopelessness, disentangling from disability, facing challenge, and achieving positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Thirdly, specialized rehabilitation institutions and multidisciplinary establishments have been inadequate in the field of SCI rehabilitation in China. Most new SCI patients have had to discharge from acute rehabilitation before they had the functional skills necessary to successfully return to the community [18]. The prevalence of anxiety in this study was 29%, which is consistent with the anxiety levels reported by hospitals (27%) and communities (29%) in a prior meta-analysis [7].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thirdly, specialized rehabilitation institutions and multidisciplinary establishments have been inadequate in the field of SCI rehabilitation in China. Most new SCI patients have had to discharge from acute rehabilitation before they had the functional skills necessary to successfully return to the community [18]. The prevalence of anxiety in this study was 29%, which is consistent with the anxiety levels reported by hospitals (27%) and communities (29%) in a prior meta-analysis [7].…”
Section: Discussionsupporting
confidence: 88%
“…However, it ignores their psychological problems and rehabilitation. As one qualitative study revealed, most individuals with SCI have experienced a series of traumas, including disabled body, a broken marriage, distress from complications, and isolation from society [18]. Thirdly, specialized rehabilitation institutions and multidisciplinary establishments have been inadequate in the field of SCI rehabilitation in China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В то же время Y. Wang и соавт. [12] выделяют три основные темы пациентов с ПСМТ: борьба с безнадежностью, принятие вызова и лич-ностный рост.…”
Section: о б з о р ыunclassified